Pengaruh Manajemen Pembelajaran Guru dan Gaya Belajar Terhadap Kreativitas Belajar Siswa SMP Yapensori Jakarta Utara - Eva Nurhayatih (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat - Islamic Institute of Syarifuddin Lumajang, Indonesia., 2020)
This study aims to determine and test empirical data related to the influence of teacher learning management and learning styles on student learning creativity in Yapensori Middle School, North Jakarta. In this study, the authors used a survey method with a correlational and regressional approach to quantitative data obtained from the research object, namely students of North Jakarta Yapensori Middle School. The sample of this research was 78 respondents from the 208 students of Yapensori North Jakarta Middle School. Data collection was carried out using a observation questionnaire, observation and regression technique which was described descriptively. The results of this study are: First, there is a positive, strong and significant relationship between teacher learning management and student learning creativity, which is shown by the simple correlation coefficient (ry.1) is 0.292 (strong correlation) and the coefficient of determination (R2) = 0.085, which means that learning management The teacher gives an influence on student creativity by 8.5% and the remaining 91.5% is determined by other factors. While the simple regression equation Å¶ = 67.752 + 0.380X1, which means that each increase in one unit of the teacher learning management score will provide a tendency towards increasing student learning creativity by 0.380. Secondly, there is a positive, quite strong and significant relationship between learning styles and student creativity, which is shown by the simple correlation coefficient (ry.2) is 0.301 (the correlation is strong enough) and the coefficient of determination (R2) = 0.090, which means that the learning style contributed to the creativity of student learning by 9.00% and the remaining 81.00% was determined by other factors. While the simple regression equation Å¶ = 70.004 + 0.344X2, which means that each increase of one unit of learning style score will provide a tendency to increase the score of student learning creativity 0.344. Third, there is a positive, strong and significant relationship between teacher learning management and learning styles together with student learning creativity, which is shown by the multiple correlation coefficient (Ry.1.2) is 0.330 (strong correlation) and the coefficient of determination (R2) = 0.109 , which means that the management of teacher learning and learning styles together provide an influence on student creativity in learning 10.9% and the remaining 89.1% is determined by other factors. Whereas the multiple regression equation Å¶ = 58,752 + 0,224X1 + 0,223X2, which means that every improvement in teacher learning management and learning styles together will provide a tendency towards increasing student creativity by 0.447.